2017
DOI: 10.1017/s0033291717002896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of between-person differences and within-person changes in symptoms of anxiety and depression on older age cognitive performance

Abstract: BackgroundAnxiety and depression are both important correlates of cognitive function. However, longitudinal studies investigating how they covary with cognition within the same individual are scarce. We aimed to simultaneously estimate associations of between-person differences and within-person variability in anxiety and depression with cognitive performance in a sample of non-demented older people.MethodsParticipants in the Lothian Birth Cohort 1921 study, a population-based narrow-age sample (mean age at wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Significant relationships between anxiety and age, nausea, and cognitive functioning were detected in patients with hematological malignancy. Consistently, it was previously reported that anxiety increase with age in healthy people [27,36,37]. The relationship between nausea and anxiety is likely identical to that of nausea and depression (explained above).…”
Section: Discussionsupporting
confidence: 82%
“…Significant relationships between anxiety and age, nausea, and cognitive functioning were detected in patients with hematological malignancy. Consistently, it was previously reported that anxiety increase with age in healthy people [27,36,37]. The relationship between nausea and anxiety is likely identical to that of nausea and depression (explained above).…”
Section: Discussionsupporting
confidence: 82%
“…Results also extended an early seminal cross-sectional study [98] which observed that whereas patients with (vs. without) depression performed poorly on auditory and visual WM tasks, patients with anxiety disorders attained scores comparable to healthy controls. Findings also built on hierarchical linear modeling results that whereas inverse EF-depression relations tended to predominate within persons, negative EF-anxiety associations tended to be larger between persons [99]. The divergence between within-and between-person findings for anxiety is likely due to the fact that between-person analyses do not account for individual differences in person-specific changes across time.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 shows the model parameter estimates for the RI-CLPM evaluating the cross- Findings also built on hierarchical linear modeling results that whereas inverse EF-depression relations tend to predominate within-persons, negative EF-anxiety associations tend to be larger between-persons (100). The divergence between within-and between-person findings for anxiety is likely due to the fact that between person analyses do not account for individual differences in person-specific changes across time.…”
Section: Lagged Relations Between Anxiety Severity and Executive Functionmentioning
confidence: 99%
“…Two papers examined the relationship between anxiety and self-efficacy and the cognitive level [25,26]. The cognitive functions considered in the studies were as follows: seven studies examined memory and/or executive process [3,10,[21][22][23][24]27]; two studies indicated a linked engagement bias for emotional information [11,20]; two papers considered compensation strategies or computer use levels [25,26]. most of the studies were conducted as cohort type longitudinal studies rather than phenomenological analyses.…”
Section: Experimental Condition To Compare Anxiety and Task-oriented Cognitive Functionmentioning
confidence: 99%
“…Four studies showed that cognitive problems in people with anxiety depend on the severity of anxiety: mild anxiety seems to affect cognitive functioning positively. However, some studies indicated that the coexistence of symptoms of anxiety and depression was associated with deficits in semantic memory, episodic memory and processing speed/shifting attention [22][23][24]27]. although previous studies have referred to the relationship between anxiety, memory and executive functioning, the results are inconsistent or partial.…”
Section: Experimental Condition To Compare Anxiety and Task-oriented Cognitive Functionmentioning
confidence: 99%